Analysis of Accounting Application on Micro Small and Medium Enterprises - Asirah, Andi; Triseptya, Ghaliyah Nimassita; Alamsyah, Muh. Fikran (Universitas Patria Artha, 2018)
Accounting is an information system that generates reports to interested parties regarding theeconomic activity and condition of the company. Micro Small and Medium Enterprises(MSMEs) as the support of the nation's economy to date still many who have not appliedaccounting in running their business. This study aims to determine and analyze the applicationof accounting on Small and Medium Micro Enterprises (SMEs) and the constraints faced in it.This research took 100 UMKM in Makassar City with descriptive analysis method by usingqualitative approach. The data used are primary data obtained through interviews andquestionnaires. The results showed that most MSMEs in Makassar have recorded the sale,purchase, other costs. While the reporting made include sales reports, purchases. Constraintsthat hamper SMEs in the application of accounting, among others, is the educationalbackground, has never been accounting training and there is no need for the application ofaccounting.